ANALISIS PERAN PEMERINTAH DAERAH TERHADAP PEMBANGUNAN INFRASTRUKTUR SEBAGAI UPAYA MENDORONG PERTUMBUHAN EKONOMI DI PROVINSI LAMPUNG - Jannah, Miftakhul; Kurniati, Erlin (Laboratorium Riset Ekonomi, 2025)
Infrastructure development has a strategic role in driving the economic growth of a region. Local governments have the responsibility to plan, manage, and implement infrastructure policies to improve connectivity, investment, and community welfare. This study aims to analyze the role of Lampung Province's local government in infrastructure development and its impact on economic growth. The research method used includes a qualitative approach with secondary data analysis from various related sources. The results show that infrastructure development policy in Lampung focuses on improving transportation networks, public facilities, and inter-regional connectivity. However, there are several challenges such as budget constraints, inter-agency coordination, and regulatory barriers. Therefore, more effective strategies are needed in infrastructure management, including collaboration with the private sector and optimization of regional budgets. With an optimized role of local government, infrastructure development can be a driver of sustainable economic growth in Lampung Province.